Recent Advances in Phototrophic Prokaryotes - Hallenbeck, Patrick C. (Advances in Experimental Medicine and Biology, 2010)
This volume is based on ISPP2009, and presents selected invited works, reviews and research articles, covering the spectrum of the diverse subject matter covered by this symposium series. Here the authors have greatly expanded on what was presented in Montreal to ensure complete coverage of each topic, covering the gamut from ecology, physiology, proteins and genomics, signal transduction, to applied aspects. Not only are these articles timely, presenting up-to-date published and unpublished results, but, since they are extensively referenced, should serve as valuable source material for some time to come.